Numerical analysis of strongly coupled multicore photonic crystal fibres for multiplexer and de-multiplexer applications. Issue 1 (1st August 2022) - Mohammed, M; Ahmad, A K
Abstract: In this study, the coupling properties of multicore photonic crystal fibers (MCPCFs) are analyzed numerically using COMSOL Multiphysics 5.5, based on the finite element method. The dependence of the coupling properties on the structure of the MCPCFs and the wavelength are investigated to realize applications such as multiplexers-demultiplexers for wavelength division multiplexing. The effective mode indexes and transverse electric field distributions of multiple cores are evaluated for different spatial configurations of identical and non-identical cores. A slight change in the central core diameter relative to adjacent cores leads to non-identical cores that lead to wavelength-dependent coupling properties, such as the coupling lengths and strength of the coefficients. The results show that the coupling lengths become longer and the strength coefficients become smaller as the wavelength decreases for non-identical cores than the identical cores. The introduction of anisotropy to all core diameters shows that the coupling lengths become longer and the strength of the coefficients become smaller as the wavelength decreases as well, and both values become lower than the ones for non-identical cores. These results prove that coupling lengths of MCPCF couplers are significantly shorter in μm compared to conventional multicore optical fiber couplers.